2011
DOI: 10.1021/jp208267p
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of Flexible Dye-Sensitized Solar Cells: Electrodeposition of Mg(OH)2 on a Nanocrystalline TiO2 Electrode

Abstract: Nanocrystalline TiO2 photoanodes were prepared on a conductive indium–tin oxide coated polyethylene naphthalate (ITO-PEN) plastic substrate by the doctor-blade method to fabricate flexible dye-sensitized solar cells (DSCs). The surface of the photoanode was coated with Mg(OH)2 by electrodeposition and the deposition time was systematically varied (2, 4, 6, 8, and 10 min). Electrodeposited Mg(OH)2 was confirmed by IR and energy dispersive X-ray (EDX) analysis. The surface morphology was studied by scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 35 publications
0
37
1
Order By: Relevance
“…Note that the performance of the cells observed in Fig. 5a are lower than in our previous work 14 due to the use of a LED light source. When solar simulated light is used similar results to 90 those reported were obtained (Fig.…”
Section: Effects Of Mg(oh) 2 Coatingcontrasting
confidence: 61%
“…Note that the performance of the cells observed in Fig. 5a are lower than in our previous work 14 due to the use of a LED light source. When solar simulated light is used similar results to 90 those reported were obtained (Fig.…”
Section: Effects Of Mg(oh) 2 Coatingcontrasting
confidence: 61%
“…The images showed that the substrates are completely covered by electrodeposited flower-like Mg(OH) 2 spheres [13,27]. Figure 2c,d shows the cross-sectional images of devices C and D respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the effect of MgO on the photovoltaic performance of printable PSCs During the electrodeposition of Mg(OH)2 in the devices B, C and D, the below electrochemical reactions could take place at the cathode surface [13], During the electrodeposition of Mg(OH) 2 in the devices B, C and D, the below electrochemical reactions could take place at the cathode surface [13],…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations